Eco-evolutionary modelling of global vegetation dynamics and the impact of CO2 during the late quaternary: insights from contrasting periods - Zhao,J; ZHOU,B; Harrison,SP; Prentice,IC (Earth System Dynamics, 2025)
Changes in climate have had major impacts on global vegetation during the Quaternary. However, variations in CO2 levels also play a role in shaping vegetation dynamics by influencing plant productivity and water-use efficiency, and consequently the relative competitive success of the C3 and C4 photosynthetic pathways. We use an eco-evolutionary optimality (EEO) based modelling approach to examine the impacts of climate fluctuations and CO2-induced alterations on gross primary production (GPP). We considered two contrasting periods, the Last Glacial Maximum (LGM, 21,000 years before present) and the mid-Holocene (MH, 6,000 years before present) and compared both to pre-industrial conditions (PI). The LGM, characterised by generally colder and drier climate, had a CO2 level close to the minimum for effective C3 plant operation. In contrast, the MH had warmer summers and increased monsoonal rainfall in the northern hemisphere, although with a CO2 level still below PI. We simulated vegetation primary production at the LGM and the MH compared to the PI baseline using a light-use efficiency model that simulates GPP coupled to an EEO model that simulates leaf area index (LAI) and C3/C4 competition. We found that low CO2 at the LGM was nearly as important as climate in reducing tree cover, increasing the abundance of C4 plants and lowering GPP. Global GPP in the MH was similar to the PI (although greater than the LGM), also reflecting CO2 constraints on plant growth despite the positive impacts of warmer and/or wetter climates experienced in the northern hemisphere and tropical regions. These results emphasise the importance of taking account of impacts of changing CO2 levels on plant growth to model ecosystem changes.